Precocious puberty in children - diagnosis, causes and treatment - Krupa, Adrianna; Piasek, Ewa; Padała, Olga; Putowski, Maciej; Konopelko, Michał (Journal of Education, Health and Sport, 2019)
Physiological sexual maturation begins with pulsatile gonadoliberin (GnRH) secretion by neurons in the arcuate hypothalamic nuclei. GnRH affects the synthesis and pulsatile secretion of the anterior pituitary gonadotropic hormones - LH and FSH, which through stimulation of the gonads lead to the production and secretion of sex hormones - estrogens and testosterone. Sex hormones are responsible for the development of secondary and tertiary sexual characteristics. The mechanisms responsible for inhibiting GnRH secretion in pre-pubertal children have not been fully understood, but they are most likely the result of homeostasis prevailing between neuronal excitatory and inhibitory systems. The entire course of puberty in children is a complex process and is influenced by a wide range of environmental and individual factors. This translates into a large range of physiological age limits for the onset of puberty: in girls between 8 and 13 years of age (on average 10 years), while for boys between 9 and 14 years of age (on average 12 years). Many factors are responsible for precocious puberty in children. The course of the disease affects both the physical and psychological sphere of the child. In order to compensate for the distant effects of this disease, it is necessary to detect symptoms early and implement effective treatment to avoid long-term complications. Emphasis should also be placed on health education to raise public awareness.